Arbitrators: appointment and removal - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
Arbitrators have some expertise in the field of the dispute and they come from different educational and professional backgrounds including law, accounting, insurance, finance, health care, engineering, architecture and construction. In fact, many arbitrators are retired or former judges and lawyers and the arbitration agreement may specify the qualifications of potential arbitrators. In Malaysia, a person aspiring to be an arbitrator will have to fulfil the stringent requirements set by the Asian International Arbitration Centre (AIAC) which include having tertiary education, sufficient experience in arbitration and any membership or accreditation from any professional membership organisation for Alternative Dispute Resolution. When empanelled with the AIAC, he/she will be bound by the AIAC’s Code of Conduct for Arbitrators.